A flattening oxygen consumption trajectory phenotypes disease severity and poor prognosis in patients with heart failure with reduced, mid‐range, and preserved ejection fraction. (6th February 2018) - Popovic, Dejana; Arena, Ross; Guazzi, Marco
Abstract : Background: In heart failure (HF), a flattening oxygen consumption (VO2 ) trajectory during cardiopulmonary exercise test (CPET) reflects an acutely compromised cardiac output. We hypothesized that a flattening VO2 trajectory is helpful in phenotyping disease severity and prognosis in HF with either reduced (HFrEF), mid‐range (HFmrEF), or preserved (HFpEF) ejection fraction. Methods and results: Overall, 319 HF patients (198 HFrEF, 80 HFmrEF, and 41 HFpEF) underwent CPET. A flattening VO2 trajectory was tracked and defined as an inflection of VO2 linearity as a function of work rate with a second slope downward inflection >35% extent of the first one. Peak VO2, the minute ventilation/carbon dioxide production (VE/VCO2 ) slope, and the presence of exercise oscillatory ventilation (EOV) were also determined. Pulmonary artery systolic pressure (PASP) and tricuspid annular plane systolic excursion (TAPSE) were measured by echocardiography. A flattening VO2 occurred in 92 patients (28.8%). PASP and TAPSE at rest were significantly higher and lower ( P < 0.001), respectively. The primary outcome was the combination of all‐cause death, heart transplantation and left ventricular assist device implantation. The secondary outcome was the primary outcome plus hospitalization for cardiac reasons. In the multivariate model including peak VO2, VE/VCO2 slope, EOV and VO2 trajectory, a flattening VO2 trajectory and EOV were retained in the regression for primary (X 2 = 35.78, and 36.36, respectively; P < 0.001) and secondary (X 2 = 12.45 and 47.91, respectively; P < 0.001) outcomes. Conclusions: Results point to a flattening VO2 trajectory as a likely new and strong predictor of events in HF with any ejection fraction. Given the relation of right‐sided cardiac dysfunction to pulmonary hypertension, this oxygen pattern might suggest a real‐time decrease in pulmonary blood flow to the left heart.